2007
DOI: 10.1002/jso.20906
|View full text |Cite
|
Sign up to set email alerts
|

Screening for basal marker expression is necessary for decision of therapeutic strategy for triple‐negative breast cancer

Abstract: Background: Triple-negative breast cancer (estrogen receptor-negative, progesterone receptor-negative and Her2-negative) can be classified into two subtypes: basal and non-basal phenotype. Among these subtypes the basal phenotype is associated with poor outcome. Ordinarily, clinicopathological testing involves only screening for ER, PgR and Her2, and for this reason the therapeutic approach that is decided for triplenegative disease is usually the same regardless of the subtype. Methods: Immunohistochemical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 23 publications
(63 reference statements)
1
33
1
1
Order By: Relevance
“…In the present study, no statistically significant association could be seen between prognostic parameters considered here and the two subtypes in agreement with some studies (Niwińska et al, 2010;Choccalingam et al, 2012). Conversely several studies have shown that the basal type is associated with tumor size and nuclear grade (Nishimura and Arima, 2008;Sasa et al, 2008;Iwase et al, 2010). Our limited study population may be the reason behind non-association.…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, no statistically significant association could be seen between prognostic parameters considered here and the two subtypes in agreement with some studies (Niwińska et al, 2010;Choccalingam et al, 2012). Conversely several studies have shown that the basal type is associated with tumor size and nuclear grade (Nishimura and Arima, 2008;Sasa et al, 2008;Iwase et al, 2010). Our limited study population may be the reason behind non-association.…”
Section: Discussionsupporting
confidence: 87%
“…The use of expanded surrogate immunopanels including CK 5/6 and EGFR has been suggested recently to exclude nonbasal cases, which have better outcomes than basal cases. 32,33 The survival differed significantly between the TNBC patients who were positive for basal markers (CK5/6 1 /EGFR 1 ) and the other patients (Supp. Info.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 1726 tumours informative for ER, PR and HER2, 282 (16.3%) showed a triple-negative phenotype. Of these, 165 tumours expressing one or more of the basal markers (CK5/6, CK14, CK17 and/or EGFR) 3,[18][19][20] and with haematoxylin-andeosin-stained slides containing sufficient tumour for assessment were included in this study.…”
Section: Methodsmentioning
confidence: 99%